Level of Involvement of Young Citizens in PTKIN Region III Cirebon and Implementation of Good Governance in Cirebon City - Fuad, Varidlo (Jurnal Ilmu Politik dan Pemerintahan, 2024)
The discourse on preparing the next generation of the nation (smart and good citizens) is not spared as something that is considered important especially in realizing the golden generation in 2045. The involvement of young citizens in political and government activities is the essence of the life of a developing democracy in Indonesia. On the other hand, the pattern of implementing government that emphasizes good governance requires harmonization between citizens and the government to produce good governance. in Cirebon City. This research is quantitative descriptive research, using a survey method. The research instrument used was a questionnaire given to 119 respondents (yount table) and having the criteria of being a student who lives and is domiciled in the Regency and City of Cirebon. The results showed that the involvement of young citizens in the PTKIN environment in Region III Cirebon and the implementation of good governance in Cirebon City were mostly at the high category level of 107 students (89.92%) of a total of 119 students.